Isolation, Purification and Some Properties of an Extracellular PHBV Depolymerase from Streptomyces omiyaensis SSM 5670 - Yashchuk, Oxana (2014)
–Streptomyces sp. SSM 5670 with the ability to degrade a natural polymers, polyhydroxyalkanoates (PHAs), showed a high activity of the extracellular poly (3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) depolymerase when it was grown in a basal medium containing PHBV as the sole carbon source. The extracellular PHBV depolymerase of the organism could be purified to electrophoretic homogeneity by ion exchange column chromatography and gel filtration approximately 10.5-fold. The recovery of its activity was 20.5%. The molecular mass of the PHBV depolymerase was estimated to be 24 kDa. The maximum activity was observed near pH 7.5 and 30°C, the activity was lost at temperatures above 45°C. This enzyme might be used to promote the degradation of PHBV products buried in soil, stabilized compost or other environments around room temperature.